The impact of innovation strategies on export performance, a case study: textile industry - Yeganegi, Kamran; Najafi, Afshin (International Journal of Scientific Research and Management (IJSRM), 2022)
To compete in foreign markets, an exporting company must achieve certain advantages that must necessarily be valuable and rare. Exporting textile products is very important as an important strategy to expand the product supply market from limited domestic markets to large foreign markets. On the other hand, the importance of investing in innovation strategy when pursuing competitive advantage and growth in foreign markets is highly emphasized. This research was conducted with the aim of investigating the impact of innovation strategies on export performance in the textile industry. The current research is a descriptive-correlational and applied research. Also, from the theoretical point of view, it is considered as one of the proof researches and from the point of view of reasoning, it is considered as one of the inductive researches. In this research, two library and field methods were used to collect information. The questionnaire was designed by the researcher based on the model taken from the research of Jude Ndubuisi Edeha et al. (2020), which includes 5 components (marketing innovation, technological innovation, product innovation, process innovation and external innovation collaboration). Also, the export performance questionnaire (Zou et al., 1998) has been used. The statistical population of this research consists of 30 experts of Savis company who are directly and indirectly engaged in export, sales and marketing, as well as 135 members of the commercial department of Arak Chamber of Commerce. The sample size was 115 people who were selected using the simple random sampling method using the sample table of Krejci and Morgan. The research hypotheses were tested using correlation and regression tests. The results of the data analysis showed that all the sub-hypotheses of the research were accepted, so it can be concluded that innovation strategies have an effect on export performance in the textile industry, and thus the main hypothesis of the research was also confirmed.